Quality of Life in Men With Prostate Cancer Randomly Allocated to Receive Docetaxel or Abiraterone in the STAMPEDE Trial. Issue 8 (10th March 2022) - Rush, Hannah L.; Murphy, Laura; Morgans, Alicia K.; Clarke, Noel W.; Cook, Adrian D.; Attard, Gerhardt; Macnair, Archie; Dearnaley, David P.; Parker, Christopher C.; Russell, J. Martin; Gillessen, Silke; Matheson, David; et al.
Abstract : PURPOSE: Docetaxel and abiraterone acetate plus prednisone or prednisolone (AAP) both improve survival when commenced alongside standard of care (SOC) androgen deprivation therapy in locally advanced or metastatic hormone-sensitive prostate cancer. Thus, patient-reported quality of life (QOL) data may guide treatment choices. METHODS: A group of patients within the STAMPEDE trial were contemporaneously enrolled with the possibility of being randomly allocated to receive either docetaxel + SOC or AAP + SOC. A mixed-model assessed QOL in those who had completed at least one QLQ-C30 + PR25 questionnaire. The primary outcome measure was difference in global-QOL (QLQ-C30 Q29&30) between patients allocated to docetaxel + SOC or AAP + SOC over the 2 years after random assignment, with a predefined criterion for clinically meaningful difference of > 4.0 points. Secondary outcome measures included longitudinal comparison of functional domains, pain, and fatigue, plus global-QOL at defined timepoints. RESULTS: Five hundred fifteen patients (173 docetaxel + SOC and 342 AAP + SOC) were included. Baseline characteristics, proportion of missing data, and mean baseline global-QOL scores (docetaxel + SOC 77.8 and AAP + SOC 78.0) were similar. Over the 2 years following random assignment, the mean modeled global-QOL score was +3.9 points (95% CI, +0.5 to +7.2; P = .022) higher in patients allocated to AAP + SOC. Global-QOL was higher for patients allocated to AAP + SOC over the first year (+5.7 points, 95% CI, +3.0 to +8.5; P < .001), particularly at 12 (+7.0 points, 95% CI, +3.0 to +11.0; P = .001) and 24 weeks (+8.3 points, 95% CI, +4.0 to +12.6; P < .001). CONCLUSION: Patient-reported QOL was superior for patients allocated to receive AAP + SOC, compared with docetaxel + SOC over a 2-year period, narrowly missing the predefined value for clinical significance. Patients receiving AAP + SOC reported clinically meaningful higher global-QOL scores throughout the first year following random assignment.